2010
DOI: 10.1364/oe.18.009220
|View full text |Cite
|
Sign up to set email alerts
|

Fidelity optimization for aberration-tolerant hybrid imaging systems

Abstract: Several phase-modulation functions have been reported to decrease the aberration variance of the modulation-transfer-function (MTF) in aberration-tolerant hybrid imaging systems. The choice of this phase-modulation function is crucial for optimization of the overall system performance. To prevent a significant loss in signal-to-noise ratio, it is common to enforce restorability constraints on the MTF, requiring trade of aberration-tolerance and noise-gain. Instead of optimizing specific MTF characteristics, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 22 publications
2
24
0
1
Order By: Relevance
“…However, we show here that the optimal value of α is considerably smaller if it is possible to optimize the image-recovery kernel as for example suggested in [10]. For a maximum W 20 of 5λ, the optimal cubic phase-modulation has α ≈ 2.8λ, a five-fold reduction on the value proposed in [1], and a correspondingly higher imaging fidelity [12].…”
Section: Variation With Defocus Tolerancementioning
confidence: 80%
“…However, we show here that the optimal value of α is considerably smaller if it is possible to optimize the image-recovery kernel as for example suggested in [10]. For a maximum W 20 of 5λ, the optimal cubic phase-modulation has α ≈ 2.8λ, a five-fold reduction on the value proposed in [1], and a correspondingly higher imaging fidelity [12].…”
Section: Variation With Defocus Tolerancementioning
confidence: 80%
“…In previously reported approaches to hybrid imaging, a range of phase functions have been reported that tend to fall into two classes: either the antisymmetric cubic and trefoil masks (or qualitatively similar shapes) or symmetric masks [14,13], and these provide complementary advantages. While the former offers a superior trade-off between enhanced DOF and noise amplification [15], the spatial-phase effects introduced by the asymmetry introduce highly problematic artifacts and also range-dependent image shifts [9] that are absent for symmetric phase functions. Here we demonstrate that, by recording images with complementary OTF characteristics, it is possible to benefit from the enhanced DOF of an antisymmetric mask but without introducing image artifacts, and combined with the enhancement of three-dimensional ranging.…”
Section: Discussionmentioning
confidence: 99%
“…Radially symmetric phase functions have also been proposed for increase of DOF, including quartic and logarithmic phase functions [13] and the logarithmic asphere [14], and these enable recovery of images without phase-induced artifacts but with higher levels of noise amplification than for the antisymmetric functions [15] for reasons that appear to be fundamentally associated with the antisymmetry [7].…”
Section: Introductionmentioning
confidence: 99%
“…By measuring the mean-squared error between the ideal and modelled restored system image, it is possible to optimise the cubic phase modulation with an efficient numerical optimisation process. Using the mean-squared error it has been demonstrated that the highest imaging fidelity can be obtained at a global optimum of β ≈ 0 and secondary optimum at β ≈ 3α [5]. The secondary optimum at β ≈ 3α has broader peak than the global optimum at β ≈ 0, which allows a greater degree tolerance with a slight movement away from the peaks.…”
Section: Optimisation Of the Wavefront Coding Surfacementioning
confidence: 99%